Pengaruh Produk, Metode Pembayaran, Kualitas Layanan Dan Kualitas Situs Web Terhadap Kepuasan Pelanggan E-Commerce Shopee Pada Mahasiswa Universitas Islam Malang - Nur Azis; Agus Widarko; Mohammad Rizal (E-JRM : Elektronik Jurnal Riset Manajemen, 2022)
AbstractThis study aims to examine and explain the effect of products, payment methods, service quality, and website quality, on e-commerce shopee customer satisfaction at the Malang Islamic University students. This research belongs to the type of associative analysis research with a quantitative approach. The method used is multiple linear regression. The sampling technique used the Slovin formula with the calculation results of 100 samples. To solve the problem in this study using SPSS assistance with validity test, reliability test, normality test, multiple linear regression analysis, multicollinearity test, heteroscedasticity test, F test, and t test. The results showed that the product, payment method, service quality, and website quality variables simultaneously had an effect on customer satisfaction. And there is a partial effect between product variables and website quality, on customer satisfaction. As well as payment methods and service quality there is no partial influence on customer satisfaction. Keywords: Product, Payment Method, Service Quality, Website Quality, Customer Satisfaction